Three-dimensional analysis of root changes after orthodontic treatment for patients at different stages of root development - Wan, Jun; Zhou, Shuduo; Wang, Jingwei; Zhang, Ruofang (American journal of orthodontics and dentofacial orthopedics, 2023)
We investigated changes in the roots of maxillary incisors at different stages of root development after fixed-appliance treatment using cone-beam computed tomography. Data from 52 subjects receiving fixed-appliance treatment were collected retrospectively. The subjects were divided into 3 groups: mixed dentition group (aged 7-10 years; root development stage: Nolla eighth-10th; n = 16), early permanent dentition group (aged 12-18 years; root development stage: Nolla 10th; n = 20), and adult group (aged 18-35 years; root development stage: Nolla 10th; n = 16). Changes in root lengths and volume of the maxillary central incisors were measured using pretreatment and posttreatment cone-beam computed tomography. The root lengths and volumes of maxillary central incisors in the mixed dentition group significantly increased after orthodontic treatment (P >0.05). No significant differences were found when comparing the final root length and volume of the mixed dentition group with the pretreatment maxillary incisor values of the early permanent dentition group (P >0.05). The early permanent dentition group showed a significant decrease in root length (P <0.05), and both the root length and volume of the adult group significantly decreased after treatment (P <0.05). The differences in root length and volume reduction between the 2 groups were not significant (P >0.05). Orthodontic treatment had no significant negative impact on the continued root development of incomplete roots with two-thirds root formation. Both the early permanent dentition and adult groups exhibited root resorption after orthodontic treatment. It seemed age was not a factor that resulted in significant root resorption during routine orthodontic leveling and alignment treatment once the roots were fully developed. •We investigated root changes of maxillary incisors after fixed-appliance treatment.•Treatment had no significant impact on the development of incomplete roots.•Age did not affect the degree of root resorption once the root had developed.